Management of displaced distal forearm fractures in children - M. Nouh, Hassan; S. Bohalfaya, Mabrouk (Libyan Journal of Science &Technology, 2024)
Distal both bones forearm fractures are quite common injury in children. They are generally treated by closed reduction and casting alone or with added percutaneous pinning with excellent results. The target of this prospective study was to delineate if re-displacement after stable reduction of displaced distal forearm fracture in a child can be prevented by percutaneous fixation with Kirschner wires. A complete of 48 children aged between 2-12 years with displaced distal both bone forearm fracture underwent either conservative treatment by immediate closed reduction and long arm cast in plaster room without anesthesia or surgical procedure by additional fixation with percutaneous Kirschner wires and long arm cast, with 28 had conservative treatment and 20 had surgery. All patients were available for follow-up with average of 6.7 months. Fractures fixed with percutaneous Kirschner wires showed no displacement, compared to three displacements within the fractures maintained by cast alone (chi-squared test, p <0.01). Range of supination and pronation is a smaller amount affected in fractures treated with pinning (6°vs.13°). Fewer complications were seen within the fractures treated by pinning than in fractures treated by cast alone (5% vs 17.8%). We conclude that the utilization of a percutaneous Kirschner wire to reinforce the reduction of the fracture in children who have a completely displaced metaphyseal fracture of the distal radius may be a safe and reliable way of maintaining alignment of the fracture. Lastly, use of percutaneous Kirschner wires to keep the reduction of the displaced distal forearm fracture in children is reliable method to stop re-displacement of the fracture.